Erratum on the article ‘Positive solutions for singular systems of higher-order multi-point boundary value problems’ (DOI: 10.3846/13926292.2013.804009) - Henderson, Johnny; Luca, Rodica (Mathematical Modelling and Analysis, 2013)
"Erratum on the article ‘Positive solutions for singular systems of higher-order multi-point boundary value problems ’ (doi: 10.3846/13926292.2013.804009)." Mathematical Modelling and Analysis, 18(3), p. 461